SISTEM INFORMASI INVENTORI PERSEDIAAN BARANG PADA PT. YASA BERKAH MANDIRI MENGGUNAKAN PHP DAN MYSQL - Akhmad Fauzan; Ertie Nur Hatiwati; Faramita Dwitama (Jurnal Teknik dan Science, 2023)
The development of computer-based information systems at this time has become a major requirement for every company on a large or small scale as a data processing system. Not infrequently the general problem of a company engaged in the procurement of goods at this time is that there are errors in several processes of processing and conveying information. Especially in the process of incoming and outgoing transactions of goods from the warehouse and then reporting the results of the transaction process and managing the inventory of goods needed by management, there are often errors and discrepancies. The purpose of this study is to produce an Inventory Inventory Information System application that is expected to be useful for the company concerned, namely to facilitate the company in carrying out the process of recording goods transactions in and out of the warehouse and produce more accurate report data. The research method used is qualitative description. Results the use of PHP and MyQSL is very effective and plays a role in inputting data. Conclusions and suggestions are that the use of PHP and MyQSL can increase the effectiveness and efficiency in data processing. It is hoped that there will be good cooperation, discipline in work, and the need for system updates so that it can facilitate data entry.